Impact of credit risk on farm planning in Chiang Mai Valley, Thailand - Mohamed, Zainal Abidin; Thani, Pichit; Chiew, Eddie Fook Chong (Universiti Putra Malaysia Press, 2003)
The risk elements inherent in farming not only influence production strategies but also borrowers decision to invest capital and the willingness of lenders to supply capital. Risk associated with costs and availability of credit is an added element of farmers' portfolio risk, which can influence debt use and the resulting capital structure. Portfolio theory suggests that the model farm's risk-efficient optimal solutions, derived without credit risk, have a concentrated mix of activities. Incorporation of risk will cause a nonparallel shift of the efficient set towards higher variances for each expected value of the objective function. This study was undertaken to measure credit availability in response to risk in farm operations and its impact on risk-averse farmers by utilising a multiperiod risk-programming model. The model emphasises the relationships between credit risks and farm income risk and is used to generate risk-efficient farm plans for representative farms in Chiang Mai Valley. The risk-programming results obtained are consistent with anticipated responses. The inclusion of credit risk takes a fuller account of the overall risk positions of farmers. As risk-aversion increases as a percentage of total for both capital and operating loans, no capital loans occur at the highest risk-aversion level, leaving intact the entire reserve of capital credit. A set of 13 efficient portfolios in the intermediate portion of the E-V frontier was also generated from the risk-programming model.